The visual world of Muslim India the art, culture and society of the Deccan in the early modern era - Parodi, Laura Emilia; Eaton, Richard M.,writer of the foreword; Sardar, Marika; Simpkins, Robert Alan; Sohoni, Pushkar; Michell, George; Philon, Helen; Rotzer, Klaus; Kruijtzer, Gijs; Weinstein, Laura; Hutton, Deborah; Tucker, Rebecca; et al. (London I.B. Tauris, 2014)
Selection of papers presented at a conference 'Art, Patronage and Society in the Muslim Deccan from the Fourteenth Century to the Present Day' (4-6 July 2008) at St. Antony's College, Oxford, with support from the John Fell Fund, Barakat Trust and Alessandro Bruschettini.
Foreword Klaus Rotzer -- Omar Khalidi -- Navina Najat Haidar -- Laura E. Parodi -- Keelan Overton -- Deborah Hutton and Rebecca Tucker -- Laura Weinstein -- Gijs Kruijtzer -- Helen Philon -- Geroge Michell -- Richard M. Eaton -- Pushkar Sohoni -- Robert Alan Simpkins -- Laura Parodi -- Marika Sardar -- A Dutch Artist in Bijapur Sacred Spaces and Objects of Popular Deccani Muslmi Devotional Practices Introduction Gulshan-i 'Ishq : Sufi Romance of the Deccan Bidri Ware and the New Mughal Order The Circular Cities of the Deccan Vida de Jacques de Coutre : A Flemish Account of Bijapuri Visual Culture in the Shadow of Mughal Felicity Migrations and Cultural Transmissions in the Deccan : Evidence of Monuments at Vijayanagara Golconda's Mosques and tombs : Distribution, Chronoloogy and Meaning Variations on a Persian Theme : The Diwan of Muhammad Quli Qutb Shah and the Brith of the Illustrated Urdu Diwan The Fighting on the Wall Medieval Chaul under the Nizam Shahs : An Archaeological and Historical Investigation Deccani Guns : Features and Ornamentation The 'Great Mosque' at Gulbarga reinterpreted as the Hazar Sutun of Firuz Shah Bahmani
Includes bibliographical references (pages 341-358) and indexes.
Keywords: Islamic art -- India -- Deccan; Deccan (India) -- Antiquities